IMPLIKASI NON-CONVICTION BASED ASSET FORFEITURE SEBAGAI LANGKAH UNTUK MENGEMBALIKAN KERUGIAN NEGARA DALAM RANGKA PENANGGULANGAN TINDAK PIDANA PENCUCIAN UANG (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In the realm of criminal law acts that are prohibited and accompanied by criminal sanctions for violationsare referred to as criminal acts or criminal acts. The prohibited acts are regulated in the legislation. Especially formoney laundering crimes regulated by a separate law, namely Law Number 8 of 2010 concerning Prevention andEradication of Money Laundering Crimes, hereinafter abbreviated as the TPPU Law. Therefore, the state has theauthority to punish those who commit money laundering as stipulated in the law. Briefly, Non-Coviction BasedAssed Forfeiture, hereinafter referred to as NCB, is the seizure of assets resulting from crime without priorpunishment of the perpetrator. This seizure of assets without punishment or NCB is one of the methods introducedin the context of implementing the provisions of CHAPTER V of the United Nations Convention AgainstCorruption (UNCAC) in particular how the recovery of assets is divided into parts: (i) general provisions, (ii)prevention and detection of transfer of proceeds of crime, (iii) actions for direct return on wealth, (iv) internationalcooperation for the purpose of seizure, (vi) special cooperation, (vii) return and surrender of assets, (viii)intelligence units, (ix) bilateral and multilateral agreements and arrangements. As is known, UNCAC has now beenratified by Indonesia to become Law Number 7 of 2006 concerning Ratification of the United Nations ConventionAgainst Corruption (UNCAC). That way, UNCAC has become part of Indonesia's positive legal system.Scientific writing aims to: firstly, to find out how the conception of the principle of Non-Coviction BasedAssed Forfeiture is a step to restore state losses in the context of Money Laundering Crime. Second, to find out theImplications of Non-conviction Based Assed Forfeiture according to Indonesian Legislation.The writing of this paper uses the research method used is Normative Legal research, namely legal researchliterature, normative legal research includes research on legal principles, research on systematic law, research onthe level of vertical and horizontal synchronization, comparative law, legal history. This research is more specificto research on legal synchronization after international conventions have been ratified or accessed into legislation.From the results of this study, it can be concluded that the conception of the principle of NCB is very usefulto confiscate and take over assets from the proceeds of a crime especially the crime of money laundering inIndonesia. NCB is not related to a criminal offense so that seizures can be more quickly requested from the courtthan Criminal Forfeiture. In contrast to confiscations in criminal proceedings which require the presence of asuspect or guilty verdict, the confiscation of NCB can be carried out as quickly as possible once the governmentsuspects a connection between an asset and a criminal offense.Keywords: Implications NCB, Asset Return, Money Laundering